Brief Report: Prevalence Trend of Transmitted Drug Resistance in a Prospective Cohort of Thai People With Acute HIV Infection. (15th August 2021) - Muccini, Camilla; Pinyakorn, Suteeraporn; Sirivichayakul, Sunee; Kroon, Eugene; Sacdalan, Carlo; Crowell, Trevor A.; Trichavaroj, Rapee; Ananworanich, Jintanat; Vasan, Sandhya; Phanuphak, Nittaya; Colby, Donn J.
Abstract : Background: The greater availability of different antiretroviral therapy regimens in developing countries may influence the emergence of transmitted drug resistance (TDR). People with acute HIV infection (AHI) represent the best opportunity for real-time monitoring of TDR. This study assessed the TDR prevalence trends over time in a Thai cohort of predominantly men who have sex with men (MSM) with AHI. Methods: At the time of RV254/SEARCH010 study (NCT00796146) enrollment and before starting ART, HIV genotyping was used to identify mutations in the reverse transcriptase and protease genes. Testing for TDR mutations was obtained by a validated in-house method with TRUGENE assay in a subset. Genotype sequences were analyzed using the Stanford University HIV Drug Resistance Database. Results: Genotyping was performed for 573 participants with AHI. Their median age was 26 years (interquartile range 22–31), 97.4% were men, and 94.1% were MSM. Overall TDR prevalence was 7.0%, declining from 12.5% in 2009–2010 to 4.8% in 2017–2018. A declining resistance prevalence to nonnucleoside reverse transcriptase inhibitor emerged from 9.4% in 2009–2010 to 3.5% in 2017–2018 and to nucleoside reverse transcriptase inhibitor from 6.3% to 2.1%. Protease inhibitor resistance showed a decreased TDR level from 3.1% in 2009–2010 to 1.4% in 2017–2018. Conclusions: We report an encouraging declining trend in TDR prevalence in a Thai cohort of mainly MSM from 2009 to 2018; in 2017–2018, we observed a low TDR prevalence according to the World Health Organization definition. Abstract : Supplemental Digital Content is Available in the Text.